Social Determinants as Mediators of the Emotional State of People With Type 2 Diabetes and/or Hypertension During the COVID‐19 Pandemic in Ecuador and Spain - María José Sanchís‐Ramón; Elisa Chilet‐Rosell; Andrés Peralta; Marta Puig‐García; María Fernanda Rivadeneira; Cintia Caicedo; Ikram Benazizi‐Dahbi; Blanca Lumbreras; Montse Nicols; Ana Cebrián; Wifredo Ricart; Ester Lopez‐Miras; et al. (Health Expectations)
ABSTRACT Introduction We aimed to explore the impact of the COVID‐19 pandemic and the resulting restrictions on the emotional state of people with type 2 diabetes mellitus (T2DM) and/or hypertension in Ecuador and Spain. Given the differences in sociopolitical and socioeconomic contexts between these two countries, the research focused on how these diverse environments and their management of social policies and pandemic strategies influenced the emotional well‐being of individuals with chronic illnesses. Methods We conducted 36 semi‐structured telephone interviews between August and December 2020 with adults diagnosed with T2DM and/or hypertension (19 in Ecuador, 17 in Spain). The interviews were recorded, anonymized and transcribed for thematic analysis. This approach allowed us to systematically identify and analyse themes related to the participants' emotional experiences during the pandemic. Results The results revealed a significant deterioration in the emotional state of participants, attributable to the stress generated by the health crisis and concerns related to their chronic illnesses. The situation elicited a range of emotions among participants, from boredom and apathy to fear, uncertainty and depression. The study highlighted how the impact on emotional well‐being was shaped by the interplay between conjunctural determinants (measures to control COVID‐19 infections) and structural factors driving inequalities (social class, gender, ethnicity). Conclusion We developed a conceptual framework illustrating how measures to control COVID‐19 infections directly influenced economic, health and social determinants, which interacted with pre‐existing inequalities and had a differential impact on individuals' emotional well‐being. This framework can be useful for designing more effective and equitable social policies during future health crises, ensuring they address social needs and safeguard psychological and emotional well‐being, particularly among vulnerable groups such as those with chronic illnesses. Patient and Public Contribution Thirty‐six participants diagnosed with T2DM and/or hypertension (19 in Ecuador, 17 in Spain) contributed to the study by sharing their emotional experiences during the pandemic. Their detailed accounts enriched the research by providing valuable insights into how the pandemic affected their emotional well‐being. There was no additional involvement or contribution from the public in the design, conduct, analysis or interpretation of the study, nor in the preparation of the manuscript.